Surface Finishing Theory and New Technology - Yang, Shengqiang; Li, Wenhui; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2018)
This book focuses on the theory and techniques of free abrasive tool finishing technology. Providing analytical methods and practical technical references for the engineers involved in surface-finishing processes, it significantly contributes to improving part quality and performance while also promoting further developments in surface finishing technology. Combining a highly systematic approach, readability and novel content, it is a valuable resource for researchers and graduates working in mechanical engineering fields, especially in surface finishing.
Surface quality and finishing -- Mass finishing technology -- Magnetic abrasive finishing technology -- Fluid magnetic abrasive finishing technology -- Two-phase flow finishing technology -- Other surface finishing technology.
Keywords: Manufactures; Surfaces (Technology).; Thin films; Magnetism; Machines, Tools, Processes; Surfaces, Interfaces and Thin Film; Magnetism